Studi komparatif pengaruh kunjungan industri terhadap budaya kerja siswa SMK - Vivi Andriani; Wetria Wetria; Chika Falda Pasaribu; Darul Ilmi (Journal of Education, Cultural and Politics, 2026)
This study aims to describe students’ work culture based on their experiences participating in DUDI visits and to understand the significance of these experiences in shaping the work readiness of students at SMK Negeri 1 Baso. This study employed a qualitative approach with a descriptive research design. The research informants consisted of 11th-grade students who had and had not participated in DUDI visits, the Vice Principal for Industry Relations, guidance counselors, and the heads of vocational programs. Data were collected through observation, semi-structured interviews, documentation, and open-ended questionnaires, then analyzed using the Miles, Huberman, and Saldaña interactive model through the stages of data condensation, data presentation, and conclusion drawing and verification. Data validity was ensured through source triangulation, methodological triangulation, and member checking. The research results indicate that students who participated in DUDI visits demonstrated a better understanding of work culture values, including discipline, responsibility, cooperation, communication, integrity, initiative, and professionalism. Hands-on learning experiences in an industrial setting help shape work ethic, boost motivation to learn, and better prepare students for the workforce. This study concludes that the DUDI visit program is an effective experience-based learning strategy for instilling a work ethic and supporting the implementation of the “link and match” policy in vocational education. Therefore, the DUDI visit program needs to be implemented on an ongoing basis and integrated into the learning process, while strengthening partnerships between schools and the business and industrial sectors.